Left ventricular systolic function and initial exercise capacity—their importance for results of cardiac rehabilitation after acute coronary syndrome - Barbara Uznańska-Loch; Ewa Wądołowska; Karina Wierzbowska-Drabik; Urszula Cieślik-Guerra; Jarosław D. Kasprzak; Małgorzata Kurpesa; Tomasz Rechciński (Exploration of Cardiology, 2023)
Aim: The aim of this study was to compare initial and final exercise tolerance and to evaluate the determinants of exercise capacity improvement—after three weeks of inpatient cardiac rehabilitation. Methods: A cohort of 494 patients after acute coronary syndrome (ACS), treated with primary coronary angioplasty (age 60 years ± 10 years, 27.5% women) was studied retrospectively. Possible correlations between improvement and age, gender, body mass index (BMI), left ventricular ejection fraction (LVEF) and the initial exercise capacity (EXT1) were assessed. Results: The highest percentage of patients with improvement (43.6%) was in the medium tercile of LVEF (> 42% but ≤ 50%) and was more likely in the medium tercile of initial exercise tolerance [> 5.7 but ≤ 8.4 metabolic equivalent of tasks (METs)]. Receiver-operator characteristic (ROC) curves were developed and the following cut-off values were found: for LVEF > 43% (this value had 69.6% sensitivity in predicting improvement; the chance of improvement was 2.67 higher than in patients with LVEF ≤ 43%); for EXT1 ≤ 8.4 METs (this value had 70.8% sensitivity, the chance of improvement was 1.86 higher than in the other subgroup). No significant relationship between improvement and gender, age or BMI was found. Conclusions: The combination of LVEF > 43% and EXT1 ≤ 8.4 METs relates to the highest probability of exercise tolerance improvement after cardiac rehabilitation.